Effects of occupational therapy - led fine motor centers on fine motor skills of preschool-aged children: An evidence-based program evaluation. Issue 3 (3rd July 2021) - Buzzell, Kaylyn; Feeney, Jenna; Gentile, Lauren; Morris, Sara; Webster, Stacey; Herlache-Pretzer, Ellen
ABSTRACT: Aim: This program evaluation examined the effects of occupational therapy (OT)-led fine motor centers (FMCs) on the fine motor skills of typically-developing preschool-aged children. Methods: This program evaluation was completed with 29 children from two preschool Great Start Readiness Program classrooms. The experimental group received OT-led FMCs twice per week for 8 weeks; the control group continued with their regular curriculum. The fine motor subtest of the Miller Function and Participation Scales (M-FUN) was used to collect data regarding fine motor skills pre- and post- intervention and 6 weeks post-intervention. A two-way mixed ANOVA was utilized for data analysis. Results: Baseline M-FUN scores of the control and experimental group at pre-test were not significantly different (p>0.067). There was a significant difference between the groups at post-test and follow-up testing (p<0.006, p<0.001). The experimental group demonstrated significant differences in M-FUN scores pre- to post-test, post-test to follow-up, and pre-test to follow-up (p<0.000, p<0.000, p<0.026); there was no significant difference in control group M-FUN scores pre- to post-test or post-test to follow-up (p>0.090, p>0.060). There was a significant difference in control group scores pre-test to follow-up (p<0.011). Additionally, 85.7% of participants in the experimental group had fine motor delays at pre-test; at follow-up testing, only 7% had delays. Eighty-six percent of control group participants had fine motor delays at pre-test; 53.3% of participants still had delays at follow-up testing. Conclusion: OT-led FMCs in preschool classrooms may improve fine motor skills of preschool-aged students; additional research with a larger sample size is suggested.